Protective and risk factors associated with substance use coping among healthcare workers during the COVID-19 pandemic - Bryant, Vaughn E.; Sorna, Michael J.; Dana, Audrey; Leon, Kalie G.; Guastello, Andrea D.; Sambuco, Nicola; Huxhold, Ashley; Allen, Brandon; Cuffe, Steven P.; Mathews, Carol A.; Dale, Lourdes P. (Frontiers in Psychology, 2023)
Background: Healthcare workers (HCWs) experienced high levels of stress and mental health consequences associated with the COVID-19 pandemic, which may have contributed to unhealthy coping behaviors, such as substance use coping (SUC). This study aimed to understand the extent of and predictors of SUC.The sample consisted of 263 HCWs in North Central Florida. Univariable and multivariable logistic regression analyses investigated whether moral injury and other work risk factors, protective factors, and clinically relevant symptoms (i.e., work exhaustion, interpersonal disengagement, depression, anxiety, and/or PTSD) were associated with likelihood of SUC.Results: Clinically relevant levels of interpersonal disengagement and anxiety increased the likelihood of SUC. Mediational analyses found that interpersonal disengagement and anxiety explained 54.3% of the relationship between Self Moral Injury and SUC and explained 80.4% of the relationship between professional fulfillment and SUC.Conclusions: Healthcare supervisors should be aware that providers who are experiencing moral injury and less professional fulfillment may be experiencing significant interpersonal disengagement and anxiety, which could lead to SUC. Future studies should examine the effects of implementing targeted prevention and treatment interventions, along with longitudinal outcomes related to SUC behaviors.